Youth Understanding of Healthy Eating and Obesity: A Focus Group Study. (17th July 2013) - Sylvetsky, Allison C.; Hennink, Monique; Comeau, Dawn; Welsh, Jean A.; Hardy, Trisha; Matzigkeit, Linda; Swan, Deanne W.; Walsh, Stephanie M.; Vos, Miriam B.
Abstract : Introduction . Given the high prevalence of childhood obesity in the United States, we aimed to investigate youth's understanding of obesity and to investigate gaps between their nutritional knowledge, dietary habits, and perceived susceptibility to obesity and its co-morbidities. Methods . A marketing firm contracted by Children's Healthcare of Atlanta facilitated a series of focus group discussions (FGD) to test potential concepts and sample ads for the development of an obesity awareness campaign. Data were collected in August and September of 2010 with both overweight and healthy weight 4th-5th grade and 7th-8th grade students. We conducted a secondary analysis of the qualitative FGD transcripts using inductive thematic coding to identify key themes related to youth reports of family eating habits (including food preparation, meal frequency, and eating environment), perceived facilitators and barriers of healthy diet, and knowledge about obesity and its complications. Results . Across focus group discussions, mixed attitudes about healthy eating, low perceived risk of being or becoming obese, and limited knowledge about the health consequences of obesity may contribute to the rising prevalence of obesity among youth in Georgia. Most youth were aware that obesity was a problem; yet most overweight youth felt that their weight was healthy and attributed overweight to genetics or slow metabolism. Conclusions . Our analysis suggests that urban youth in Georgia commonly recognize obesity as a problem, but there is less understanding of the link to lifestyle choices or the connection to future morbidities, suggesting a need for education to connect lifestyle behaviors to development of obesity.